WACANA TUNA-BUDAYA DAN TUNA-SEJARAH PADA GENERASI MASA KINI - Farid Abdullah (Universitas Andalas, 2019)
This article presents a discourse on problems in our generation about culture and history today. The important issue to our generation is an inadequacy in history and culture understanding (tuna-budaya dan tuna-sejarah). History categorized as a pure science, where the research method stages start from heuristic, critic, interpretation, and historiography. Art define as a spiritual activity, and not merely physical activity, the use of skill and imagination in the creation of aesthetic objects, environments, or experiences that can be shared with others. Artistic works have existed for almost as long as humankind. Art student whose study history must creative and active. Art students should look for something creative and always search the great values for the future.Keywords: inadequacy of culture, history, art, discourse